Utilization of Agricultural Training Programmes as Trajectories for Enhanced Productivity Among Rural Farmers in Rivers State - Aleru, P. D.; Lazarus, S.T.; Onwuamaegibu O. L. (Scholars Digest Publishing, 2022)
The study examined agricultural training programmes that would enhance rural farmers’ productivity in Rivers State, Nigeria. The study was guided by three (3) research questions. The study adopted a descriptive survey research design. The target population was all peasant farmers in Rivers State. A simple random sampling technique was adopted to select 124 female and 102 male from five local government areas in the State. The instrument for data collection was a self-structured questionnaire designed in a 5-point rating scale of very high extent, high extent, low extent and very low extent with a numeric value of 5, 4, 3, 2 and 1 respectively. The instrument was scrutinized by two experts. The reliability of instrument was established using cronbach alpha reliability which yielded an index of 0.88. Data was analyzed using mean and standard deviation with a benchmark mean value of ≥ 3.00. Findings from the study revealed that training programmes such as farmer-to-farmer training, farmers’ field-school programme and enterprise training would enhance quality of information of farmers thus improving their agricultural productivity, enhance adequate adoption of new farming techniques, enhance smallholder farmers’ managerial skills and improves their skills in control of diseases in agricultural production. The study therefore recommends that these programmes be seriously implemented to boost farmers’ farm produce thus enhancing their income through production agriculture.
Keywords: Agriculture, Training Programmes, Trajectories, Productivity, Farmers.